The Implementation of Grammarly In Error Analysis Implementasi Grammarly Dalam Error Analysis - Dhion Meitreya Vidhiasi; Haryani Haryani (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2020)
English is still considered as a difficult thing to learn, both for students and teachers. That is because English is still regarded as a foreign language and is rarely used in daily conversation. The difficulty in mastering English is found not only in the speaking aspect but also in the writing element. In examining student writing (error analysis), lecturers at the Akademi Maritim Nusantara Cilacap used a program called Grammarly. This study aims to see the implementation of Grammarly in helping lecturers make Error Analysis. Researchers found that Grammarly was enough to help lecturers in conducting error analysis. Researchers then classify the types of errors found in student writing using Grammarly. From 7 (seven) student writings that were used as data sources in this study, there were 9 (nine) types of errors that were made in the writing of the seven students. The most common errors were errors with spelling (39%) and punctuation (40.3%). Although Grammarly is proven to help the work of lecturers in conducting Error Analysis, Grammarly still cannot find sentences that have errors semantically quickly.